2022
DOI: 10.3389/fchem.2022.1028957
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic mixed-ligand complexes of Cu(II): A combined experimental and computational study

Abstract: Herein, we report the synthesis of mixed-ligand Cu(II) complexes of metformin and ciprofloxacin drugs together with 1,10-phenanthroline as a co-ligand. The synthesized complexes were characterized using different spectroscopic and spectrometric techniques. In vitro cytotoxic activity against human breast adenocarcinoma cancer cell line (MCF-7) as well as antibacterial activity against two gram-negative and two gram-positive bacterial strains were also investigated. The analyses of the experimental results were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(51 citation statements)
references
References 52 publications
(68 reference statements)
3
48
0
Order By: Relevance
“…The absorption peaks (experimental/TD-DFT) at 267/261 and 320/325 nm, due to π → π* transitions of the benzoyl system and the cinnamoyl system, respectively, were reported for chrysin. For 1,10-phenathroline free ligands (experimental/TD-DFT), the absorption peaks at 228/226 and 263/258 nm due to n → π* (CN) and π → π* (CC) transitions, respectively, were reported …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The absorption peaks (experimental/TD-DFT) at 267/261 and 320/325 nm, due to π → π* transitions of the benzoyl system and the cinnamoyl system, respectively, were reported for chrysin. For 1,10-phenathroline free ligands (experimental/TD-DFT), the absorption peaks at 228/226 and 263/258 nm due to n → π* (CN) and π → π* (CC) transitions, respectively, were reported …”
Section: Resultsmentioning
confidence: 99%
“…The quantum chemical descriptors of the free ligands and the corresponding metal complexes are presented in Figure and Table S2, whereas the wave function distributions are shown in Figures and S3. In our previous study, we reported that the band gap energy ( E g ) has a strong correlation with various biological activities: antibacterial, antioxidant, and cytotoxicity. ,, Moreover, band gap energy has been used as an important stability descriptor. A compound with large band gap energy is suggested to be stable and hard, whereas that with small band gap energy is less stable, giving the compound softness and enhanced biological importance .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, the syntheses of biologically active complexes have paramount significance. Research results over the past decades have witnessed that metal complexes were found to exhibit potential antimicrobial and antioxidant ( El-Gammal et al, 2021 ; Kargar et al, 2021 ; Kaya et al, 2021 ; Damena et al, 2022a ), antiviral ( Atasever Arslan et al, 2021 ), anticancer ( Malik et al, 2021 ), antidiabetic ( Koleša-Dobravc et al, 2018 ) and cytotoxicity ( Alem et al, 2022 ) activities. In this aspect, the ongoing search for natural products with potential biologically active ligands have confirmed that quinoline and its derivative ligands lie among the important classes of biologically active ligands.…”
Section: Introductionmentioning
confidence: 99%